Who owns education? : Cleavage structures in the partisan competition over educational expansion - Busemeyer, Marius R.; Franzmann, Simon T.; Garritzmann, Julian L. (My University, 2013)
The literature on the partisan foundations of education policies leads to ambiguous expectations with regard to the predominant cleavage structures in party competition on this topic. There is disagreement as to whether leftist or rightist parties are responsible for increasing spending on education, while others claim that educational expansion has become a consensual topic. This paper analyses the cleavage structure of party competition over the topic of educational expansion, relying on data from the Comparative Manifesto Project. It identifies political parties as ‘issue-owners’ and ‘issue-ignorers’, respectively, and finds considerable variation with regard to cleavage structures of party competition between countries and across time. One tentative conclusion from the analysis is that policy legacies play an important role in shaping cleavage structures.
Keywords: Parteienwettbewerb; Partei; Bildungspolitik; Bildung; Wohlfahrtsstaat; Politische Ökonomie; Öffentliche Ausgaben; Bildungsausgaben; Konfliktlinie; Parties; Party Competition; Education; Education Policies; Education Spending; Public Spending; political economy of skill formation; welfare state analysis; 320